bakstepping and sliding mod control for a quadcopter - Kouidri Abdelhamid; Zerarka, Mounir; Sahraoui, Khaled (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electrotechnique, 2020)
The objective of this work is to present different methods for quadcopter control and their application , what are it's advantages and disadvantages , we designed a complete model of quadrotor that we used to study its behavior in different operating regimes and under different circumstances , then we presented an open loop and closed loop approach . after that we presented two leading theoretical approaches of two control techniques: backstepping control and sliding mode control.
Option : Automatic and systems